Tsallis entropy and Jaynes' Information Theory formalism - Plastino, Ángel Luis (1999)
The role of Tsalli's non-extensive Information Measure within an a la Jaynes Information-Theory-based formulation of Statistical Mechanics is discussed in rather detailed fashion.